2003
DOI: 10.1097/01.blo.0000059581.08469.77
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential and Posterolateral Fusion for Lumbar Disc Disease

Abstract: Clinical outcome of low back fusion is unpredictable. There are various reports discussing the merits and clinical outcome of these two procedures. The patients were selected from a population of patients who had chronic low back pain unresponsive to conservative treatment. Thirty-six instrumented posterolateral fusions and 35 instrumented circumferential fusions with posterior lumbar interbody fusions were done simultaneously. Preoperative radiographic assessment included plain radiographs, magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…2) A comparison study found 61% improvement in working ability in the PLF group and 77% improvement in the PLIF group with statistical significance. 17) In this study, 33% in the PLF group and 46% in the PLIF group returned to original duties. Resumption rate of full time work after PLIF has been estimated as 34% in degenerative disc disease confirmed by discography, whereas overall resumption rate to work was 62%.…”
Section: Discussionmentioning
confidence: 86%
“…2) A comparison study found 61% improvement in working ability in the PLF group and 77% improvement in the PLIF group with statistical significance. 17) In this study, 33% in the PLF group and 46% in the PLIF group returned to original duties. Resumption rate of full time work after PLIF has been estimated as 34% in degenerative disc disease confirmed by discography, whereas overall resumption rate to work was 62%.…”
Section: Discussionmentioning
confidence: 86%
“…[21][22][23] Fusion rates and clinical outcome evaluation were not the intention of this study. The immediate and short-term advantages of TLIF over AP surgery have been revealed by comparing operative data, hospitalization time, and complication rate.…”
Section: Discussionmentioning
confidence: 98%
“…Pedicle screw and/or transfacet fixation to increase torsional stability is particularly useful in the presacral ALIF approach, as it provides posterior column stability across the fusion site, and added resistance to torsion. 32,33 The presacral ALIF approach may be associated with significant complications. 17,20 Perforation of the rectal wall can occur if the presacral space is developed inadequately.…”
Section: Discussionmentioning
confidence: 99%